Overtrading as an Expression of Investor FOMO in Cryptocurrency Markets: Insights from the Monkey Business Perspective - Agda, Vincensius Raynaldy Pramudya Putra; Subagyo, Herry; Hernawati, Retno Indah (Ilomata International Journal of Management, 2026)
This study analysed overtrading behaviour as a manifestation of FOMO, influencers, market sentiment, and crypto literacy in crypto traders. Additionally, it examined the moderating role of monkey business practices in these relationships. This phenomenon is interesting because the emergence of DEXs provides transaction freedom while increasing the risk of market manipulation and behavioural bias. This study represents the first comprehensive behavioural analysis of overtrading within decentralized exchange environments, addressing a significant gap in the cryptocurrency literature. While prior research has examined behavioural factors in general cryptocurrency markets, centralized exchanges, or DEX market structures, but no study has specifically investigated how FOMO, influencers, market sentiment, and crypto literacy interact with market manipulation practices to drive overtrading behaviour on DEX platforms. The method employed was a quantitative survey of 180 DEX traders in social media groups, utilizing purposive sampling techniques. Data were analysed using PLS-SEM to test the direct influence and moderation between variables. The results indicate that FOMO, influencers, and market sentiment have a positive impact on overtrading, whereas crypto literacy has a negative effect. In addition, monkey business moderates the influence of FOMO on overtrading but does not moderate the influence of influencers, market participants, and crypto literacy. These findings enhance understanding of how psychological and social factors influence trading decisions in decentralized markets. Specifically, the moderating role of monkey business practices provides new insights for behavioural finance theory. The implications of the study confirm the importance of caution when trading crypto on DEXs.